Les « techniques alternatives » sont-elles envisagées comme un outil de gestion qualitative des eaux pluviales ? - Émeline Comby; Anne Rivière-Honegger; Marylise Cottet; Sébastien Ah-Leung; Nina Cossais (Développement Durable et Territoires)
Stormwater is a major source of nonpoint source pollutant contamination in aquatic environments. We aim at understanding how various stakeholders perceive and address the pollutant issues linked with stormwater and at analyzing what degree of efficiency they associate with alternative stormwater management facilities (centralized and decentralized). We interviewed 24 stakeholders involved in stormwater management in the metropolitan area of Lyon. The results show that stormwater management is primarily considered quantitatively. Alternative stormwater management make municipal actors and scientists think differently the city. If managers know quite well pollution, they struggle to define micropollutants. Stakeholders perceive alternative stormwater management facilities as a multifaceted reality.